Syntag treebank - Språkbanken Text (University of Gothenburg, 2024)
SynTag is a so called tree bank, containing syntactically annotated text from 158 articles from the corpus Press-65, with about 100 000 running words. The annotation contains the relations of constituents and words, such as subjects or other arguments of finite verbs, in up to 12 levels of analysis. Additionally, there are simple word tags. The data still contains some errors, which will be corrected in the future.

More information (in Swedish) about SynTag can be found in this manual.

SynTag är en s.k. trädbank, innehållande syntaktiskt märkt text från 158 artiklar ur Press-65, omfattande drygt 100 000 löpande ord. Märkningen avser endast konstituenternas och ordens relationer till varandra (t.ex. som subjekt eller annat argument till ett finit verb) och omfattar upp till 12 analysnivåer. Dessutom finns en enkel ordklassmärkning. Vissa fel kvarstår och kommer småningom att rättas.

Mer information om SynTag finns i denna manual.
Syntag trädbank
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik